Pericolosità sismica di riferimento per il territorio nazionale MPS04 - Stucchi, Massimiliano; Meletti, Carlo; Montaldo, Valentina; Akinci, Aybige; Faccioli, Ezio; Gasperini, Paolo; Malagnini, Luca; Valensise, Gianluca (Istituto Nazionale di Geofisica e Vulcanologia (INGV), 2004)
Seismic hazard values are expressed in terms of maximum horizontal component of the expected ground shaking (ag=fraction of gravity acceleration) with 10% probability of exceedance in 50 years, referred to rocky soils (Vs30>800 m/s, class A, paragraph 3.2.1 in Ministerial Decree September 14th 2005).
The ag values have been estimated according two grid points not overlapping:
a) with step 0.05 degrees, according the requirements of the Ordinance 3519 (Official Gazette n.108, May 11th 2006), with 16921 points overall;
b) with step 0.02 degrees, for a better resolution, with 104565 points overall.
For each point the standard estimate of ag (50th percentile) and the uncertainties expressed by 16th and 84th percentiles are available. Grid points are sorted from West to East and from North to South

I valori di pericolosità sismica sono espressi in termini di massima componente orizzontale dello scuotimento del suolo (ag = frazione della accelerazione di gravità) con probabilità di eccedenza del 10% in 50 anni, riferita a suoli rigidi (Vs30>800 m/s, ovvero cat.A, punto 3.2.1 del D.M. 14.09.2005).
I valori di ag sono stati calcolati su due griglie di punti non sovrapposte:
a) con passo 0.05 gradi, secondo il dettato dell’Ordinanza 3519 (GU Serie Generale n.108 del 11-05-2006), per un totale di 16.921 punti;
b) con passo 0.02 gradi, per una maggior definizione, per un totale di 104.565 punti.
Per ciascun punto vengono forniti i valori standard di ag (50mo percentile) e le misure delle incertezze espresse in termini di 16mo e 84mo percentile. I punti sono presentati in sequenza ordinata da ovest a est e da nord a sud.
Reference Seismic Hazard Map for the Italian Territory MPS04
MPS04
http://zonesismiche.mi.ingv.it/elaborazioni/docs/
Keywords: seismic hazard; peak ground acceleration